Foeniculum vulgare (Fennel): A comprehensive review of its anti-diabetic properties - Nozizwe Hillary Ncube; Jeena Gupta (Asian Pacific Journal of Tropical Biomedicine)
Type 2 diabetes mellitus (T2DM) emerges as a global health crisis and is characterized by hyperglycemia, insulin resistance, and oxidative stress. Conventional treatments for T2DM often have limitations, thus prompting interest in natural alternatives like fennel. This review explores fennel's potential anti-diabetic properties, focusing on its antioxidant and anti-inflammatory effects. Fennel contains various bioactive compounds, including flavonoids, phenolic acids, and volatile oils, known for their antioxidant properties. These compounds can neutralize free radicals and reduce oxidative stress, which plays a crucial role in T2DM. Additionally, fennel's anti-inflammatory effects may help mitigate the chronic inflammation associated with T2DM. Preclinical studies have demonstrated fennel's ability to lower blood glucose levels, improve insulin sensitivity, and reduce oxidative stress in diabetic animals. These findings suggest that fennel may be a promising natural agent for managing T2DM. However, further research is needed to fully understand its mechanisms of action and to evaluate its efficacy and safety in human clinical trials.